2019
DOI: 10.1093/crocol/otz015
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vancomycin as an Adjuvant Treatment in IBD

Abstract: Objective To study the efficacy of oral vancomycin (POV) treatment in pediatric inflammatory bowel disease (IBD). Methods We conducted retrospective and prospective chart reviews, identifying patients using the Division’s Inflammatory Bowel Disease (IBD) registry, ICD-9 and ICD-10 codes for IBD, and recall of patients receiving POV. Patients aged 2–21 years with active IBD at initiation of POV were included unless they had Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Oral vancomycin has been considered an effective medication for IBD treatment [ 10 , 11 ], compared to traditional antibiotics, vancomycin has a better side effect profile without increasing the risk for vancomycin-resistant enterococcus [ 12 , 13 ]. However, Ayers and his colleagues indicated that oral vancomycin treatment might be an effective treatment option for IBD in the short and long term [ 14 ]. In addition, Tannock et al reported that oral vancomycin treatment is effective in patients with colitis and suggested a possible relationship between its ability to treat UC and its effect on the vancomycin-sensitive bacteria in the gut microbiota [ 15 ], which affect the severity of colitis by attracting neutrophils into damaged colon tissue, thereby to increased colon inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral vancomycin has been considered an effective medication for IBD treatment [ 10 , 11 ], compared to traditional antibiotics, vancomycin has a better side effect profile without increasing the risk for vancomycin-resistant enterococcus [ 12 , 13 ]. However, Ayers and his colleagues indicated that oral vancomycin treatment might be an effective treatment option for IBD in the short and long term [ 14 ]. In addition, Tannock et al reported that oral vancomycin treatment is effective in patients with colitis and suggested a possible relationship between its ability to treat UC and its effect on the vancomycin-sensitive bacteria in the gut microbiota [ 15 ], which affect the severity of colitis by attracting neutrophils into damaged colon tissue, thereby to increased colon inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%